Investigating the Relationship Between Intelligent Automation and Supply Chain Resilience Based on the Role of Integration Capability - Heydari, Mokhtar (Management Strategies and Engineering Sciences, 2027)
This study was conducted to investigate the relationship between intelligent automation and supply chain resilience based on the role of integration capability and supply chain transparency. The statistical population included managers and experts employed in large industries in Iran. The research questionnaire was distributed among 384 members of the statistical population selected as the sample, and the completed questionnaires were collected. The data gathered through the questionnaires were analyzed using SPSS version 24 and AMOS version 24 software through structural equation modeling. The results indicated that intelligent automation has a positive and significant effect on supply chain resilience. Supply chain integration plays a positive mediating role in the relationship between intelligent automation and supply chain resilience. Supply chain transparency also plays a positive mediating role in the relationship between intelligent automation and supply chain resilience.